Education on The Use of Antibiotics to Reduce Resistance Rates in Integrated Coaching Post for The Elderly - Koniah, Eni; Gunawan, Dewi Oktavia; Elfrieda, Nyayu Siti Aminah Lily; Sa'adah, Aas (Jurnal Pengabdian Masyarakat Inovatif, 2024)
Antibiotic resistance is a serious public health problem because it has the potential to pose a serious threat to health services if not treated, and could trigger another pandemic. The use of antibiotics in Indonesia is quite high and inappropriate, this will increase the incidence of resistance. Antibiotic resistance is reported to increase in direct proportion to the increase in consumption, this occurs due to irrational use of antibiotics and inadequate public education. Therefore, this community service activity is carried out with the aim of providing education to increase and expand public knowledge about the correct use of antibiotics, as well as to increase public awareness about the importance of using antibiotics correctly to reduce the incidence of resistance. The method used to provide education in the lecture method using LCD (Liquid Crystal Display) and Leaflet media, to present information on the correct use of antibiotics. Respondents are given the opportunity to ask questions followed by discussion. To measure the level of knowledge, 30 respondents were asked to answer 15 questions in a list of questions related to the material provided. The results showed that before education the knowledge level category was good as many as 18 respondents (60%), after education it increased to 29 respondents (96.0%), the knowledge level category was not good before education as many as 12 respondents (40.0%), after education it became 1 respondent (3.0%).  The conclusion is that there is an increase in knowledge among respondents who are educated about how to use antibiotics correctly.